Foyle's war. Set 4 [videorecording (DVD)] - Millar, Gavin; Silberston, Jeremy; Kitchen, Michael, 1948-; Howell, Anthony, 1971-; Weeks, Honeysuckle, 1979- (Distributed by Acorn Media, 2009)
History meets mystery in this PBS series, with four feature-length episodes set at the height of World War II. War has torn the social fabric of the once quiet coastal community of Hastings and DCS Christopher Foyle's investigations explore the violence and opportunism that the conflict has fostered on the home front.